Antimesenteric cutback end‐to‐end isoperistaltic anastomosis (Sasaki‐Watanabe anastomosis) for Crohn's disease: Novel surgical technique and early results of surgical anastomotic recurrence. Issue 4 (15th February 2021) - Watanabe, Kazuhiro; Sasaki, Iwao; Kohyama, Atsushi; Suzuki, Hideyuki; Kobayashi, Minoru; Kajiwara, Taiki; Karasawa, Hideaki; Ohnuma, Shinobu; Kamei, Takashi; Unno, Michiaki
Abstract: Background: Antimesenteric cutback end‐to‐end isoperistaltic anastomosis (Sasaki‐Watanabe anastomosis; Sasaki‐W anastomosis), which was developed in our department, is a novel hand‐sewn anastomotic technique for Crohn's disease intended to prevent anastomotic stenosis and preserve the peripheral circulation. Aim: The aim of the present study is to present the surgical technique of Sasaki‐W anastomosis and to assess the safety and the early results of the surgical anastomotic recurrence of Sasaki‐W anastomosis. Patients and Methods: The present study was a single‐center retrospective cohort study. As an early‐period group, 13 patients with Crohn's disease, who were mainly selected from cases considered to be at high risk of recurrence, underwent 15 Sasaki‐W anastomoses from August 2009 to January 2012. As a late‐period group, 36 patients with Crohn's disease, who were selected regardless of risk factors, underwent 37 Sasaki‐W anastomoses from September 2016 to March 2020. The medical data including patient characteristics, surgical records, postoperative details, and surgical recurrences were assessed. Results: There were no intraoperative complications. With a median follow‐up of 107 mo, surgical recurrence occurred in one patient at 106 mo after surgery in the early‐period group. The cumulative surgical recurrence‐free rate in the early‐period group was 100% at 5 y and 86% at 10 y after surgery. No patients required reoperation in the late‐period group. Conclusion: Sasaki‐W anastomosis is safe and feasible. Although long‐term study is needed, this anastomotic technique can be a reasonable operative option for Crohn's disease. Abstract : Antimesenteric cutback end‐to‐end isoperistaltic anastomosis (Sasaki‐Watanabe anastomosis; Sasaki‐W anastomosis) is a novel hand‐sewn anastomotic technique for Crohn's disease intended to prevent anastomotic stenosis and preserve the peripheral circulation. Here we show the surgical technique and early results of surgical anastomotic recurrence.